The effect of level of knowledge accuracy of results on learning of motor skills in children and adults - N.B. Beltrão; R.S. Henrique; A.K.M. Siqueira; J.N.C. Santos; A.M.S. Mello; M.T. Cattuzzo (Desafio Singular, 2011)
The level of knowledge accuracy of results (KR) is a variable that interferes with the learning of motor skills, however such interference does not work the same way in adults and children. This study examined the effects of KR in children and adults during learning of a manipulative task with target accuracy. Forty adults (female = 21.13 ± 2.26 years; male = 20.97 ± 2.17 years) and forty children (female = 9.10 ± .83 years; male = 9.70 ± .48 years) practiced a task of hitting a target placed on a table by the thrown of metal discs. There were six experimental groups and two control groups (without KR) containing 10 subjects each. Experimental groups differed according to the individual's KR (less precise KR, precise KR and very precise KR) and development level (children and adult). Performance measure was the absolute error (AE). A three-way (age × groups × blocks) and two-way (groups × blocks) analysis of variance for the stabilization and adaptation phases were used. Results showed that adults perform better than children in low and intermediate KR and in high KR adults and children showed similar performance.